2017
DOI: 10.1186/s13063-017-2139-5
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study exploring the combination of radiotherapy with two types of acupuncture treatment (ROSETTA): study protocol for a randomized controlled trial

Abstract: BackgroundAdverse effects such as fatigue, pain, erythema, nausea and vomiting are commonly known in patients undergoing irradiation (RT) alone or in combination with chemotherapy (RCHT). Patients suffering from these symptoms are limited in their daily life and their quality of life (QOL) is often reduced. As addressed in several trials, acupuncture can cause amelioration of these specific disorders. Especially for pain symptoms, several groups have shown efficacy of acupuncture. To what extent the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This, in turn, can be improved and supported by adding CAM to standard cancer treatment, as shown by several studies. In general medical oncology, a large quantity of studies exist showing that, e. g., pain, nausea, fatigue, and depression are improved using CAM treatments such as acupuncture, sports, and dietary supplements [6,[14][15][16][17][18][19][20]. However, in our cohort of surveyed radiation oncologists, we found that more evidence of CAM effectiveness and safety is still needed before CAM would be recommended without hesitation [3,21,22].…”
Section: Discussionmentioning
confidence: 80%
“…This, in turn, can be improved and supported by adding CAM to standard cancer treatment, as shown by several studies. In general medical oncology, a large quantity of studies exist showing that, e. g., pain, nausea, fatigue, and depression are improved using CAM treatments such as acupuncture, sports, and dietary supplements [6,[14][15][16][17][18][19][20]. However, in our cohort of surveyed radiation oncologists, we found that more evidence of CAM effectiveness and safety is still needed before CAM would be recommended without hesitation [3,21,22].…”
Section: Discussionmentioning
confidence: 80%
“…RT is the main pillar in cancer care, offering curative treatment for several indications. Despite the vast benefits derived from the various medical applications of RT, RT-related side effects sometimes develop [10]. Any agent that can decrease its toxicity to normal cells would therefore be of great value in reducing the very unpleasant side effects that cancer patients receiving RT can experience.…”
Section: Discussionmentioning
confidence: 99%
“…Homb et al [42] performed a retrospective analysis of combination acupuncture for xerostomia on 16 patients, thus below the prespecified threshold of 20 subjects upon inclusion in our study. For the same reason, the interimreport [43] on first 15 patients enrolled in a randomized trial assessing the impact of acupuncture on acute toxicity during CRT was also excluded, whereas the publication on the controlled, randomized Rosetta trial [44] had no patient information. Overall, 5 articles published between 2011 and 2019 fulfilled our inclusion criteria and were retained in the final analysis (Table 1).…”
Section: Data Collection and Analysismentioning
confidence: 99%